X+(x+2)+(x+4)=-15

Simple and best practice solution for X+(x+2)+(x+4)=-15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+(x+2)+(x+4)=-15 equation:


Simplifying
X + (x + 2) + (x + 4) = -15

Reorder the terms:
X + (2 + x) + (x + 4) = -15

Remove parenthesis around (2 + x)
X + 2 + x + (x + 4) = -15

Reorder the terms:
X + 2 + x + (4 + x) = -15

Remove parenthesis around (4 + x)
X + 2 + x + 4 + x = -15

Reorder the terms:
2 + 4 + X + x + x = -15

Combine like terms: 2 + 4 = 6
6 + X + x + x = -15

Combine like terms: x + x = 2x
6 + X + 2x = -15

Solving
6 + X + 2x = -15

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + X + -6 + 2x = -15 + -6

Reorder the terms:
6 + -6 + X + 2x = -15 + -6

Combine like terms: 6 + -6 = 0
0 + X + 2x = -15 + -6
X + 2x = -15 + -6

Combine like terms: -15 + -6 = -21
X + 2x = -21

Add '-2x' to each side of the equation.
X + 2x + -2x = -21 + -2x

Combine like terms: 2x + -2x = 0
X + 0 = -21 + -2x
X = -21 + -2x

Simplifying
X = -21 + -2x

See similar equations:

| 5x-8=11+7x-2 | | 0.75x+25=250.00 | | (X+1)(8x)=a | | 2(3x-3)=3(2x+2) | | 5y=-1x-3 | | r=2t+3 | | 8x=16+27 | | 2*(3x-8)+14=16 | | x*20/100=158 | | 2(3x-8)+14=16 | | x/6--1/x=1/3 | | x-20.7=9.5forx | | -8v=-9v+2 | | 7x-11=2(1-x) | | 3n+2n-4n= | | 20x-y=60 | | -4f+6=-6f | | 2m=3m+7 | | -4+3z=z | | 10+k=-k | | 4r=-3+3r | | 7+8w=9w | | 7w=6w+7 | | 2u=-2+u | | (6h+2)+(7h-8)= | | 2x(x+1)=8 | | 3(z-3)=3(z-4) | | Bx-cx=7 | | 8x-x-6=1/2 | | 20x^2-24x-120=0 | | (60-3x)(x+3)=0 | | 47+n+18=14 |

Equations solver categories